Current Accounts : What Is Their Relevance for Economic Policymaking? - Scacciavillani, Fabio (IMF Working Papers; Working Paper ;, 1998)
This paper surveys the main theoretical approaches for analyzing movements in the current account of the balance of payments, from the Mundell-Fleming paradigm to modern intertemporal approaches. It discusses the main implications of these analyses for policymaking, highlighting that modern economic theory views current account imbalances not simply as a reflection of goods market developments, but also as an outcome of intertemporal consumption and investment choices and associated capital market behavior. To reflect on the policy strategies applied under diverse circumstances, the paper analyzes the recent experiences of Italy, Israel, and Pakistan.